THE INFLUENCE OF TRUST AND SATISFACTION ON LOYALTY CUSTOMERS AT UKM DNA COLLECTION SUMENEP CITY - Rifki Abrory; Fullchis Nurtjahjani; Yosi Afandi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The rapid flow of globalization and lots of competition require enhancing product quality, providing excellent service and increasing marketing. Based on observations, UKM DNA Collection Sumenep City has done something so that customers trust the UKM, and customers feel satisfied with UKM DNA Collection, but sales are still declining. The purpose of this research is to examine the partial and simultaneous influence of trust and satisfaction on customer loyalty. This research was explanatory research with a quantitative approach carried out by distributing questionnaires to 100 respondents in January-March 2024 with the criteria of customers who have made at least 2 purchases at UKM DNA Collection using a purposive sampling technique. Data analysis uses multiple linear regression analysis. According to the findings of the partial hypothesis test, client loyalty are positively and significantly impacted by trust, and subsequently by customer satisfaction. The results of simultaneous hypothesis testing shows that trust and satisfaction has a positive and significant effect on customer loyalty by 43.1% and the remaining 56.9% are influenced by other factors not discussed in this research. From the results of this research it can be concluded that trust and satisfaction influence customer loyalty in UKM DNA Collection Sumenep City. DNA Collection needs to increase integrity and optimize satisfaction through willingness to recommend.